Editorial. Issue 157 (March 2016) - Gustafsson, Jan-Ake; Webb, Paul
Abstract: This Special Issue on the topic of "Orphan Nuclear Receptors" should help to cement the long held view that orphan members of the Nuclear Receptor superfamily play crucial roles in development, physiology and multiple pathologies and that some are attractive druggable targets. Focusing on selected orphans, this issue highlights recent developments in orphan receptor action and addresses questions about function, ligand recognition, strategies for drug development and applications for such drugs. This article is part of a Special Issue entitled "Orphan Nuclear Receptors".